Republic of Korea : Economic and Policy Developments. (IMF Staff Country Reports; Country Report ;, 2000)
The primary focus of this paper is on economic developments and policies in the period since the outbreak of the financial crisis. Policies adopted under the program successfully restored external stability, rebuilt reserves, and initiated reform of the financial and corporate sectors. Key indicators point to continued economic expansion. Several measures have been implemented to ease the foreign exchange and domestic liquidity constraints putting in place a working social safety net. The paper also discusses financial sector restructuring and corporate sector reforms under way in Korea.